Application of Sharia Principles in Sharia Financial Institutions - Fadia Fitriyanti; M. Fabian Akbar; Andi Pramudya Syamsu; Reksa Fikri Nurhaifa (Universitas Lampung, 2023)
This study analyzes related to Islamic Financial Institutions (LKS). Which currently exists and is growing quite rapidly. There have been numerous variations of LKS throughout Indonesia, including Islamic institutions. LKS is a financial institution that operates following Sharia law. LKS, a financial institution with Sharia principles, was originally present as an option and a solution for Muslims who want to avoid the practice of conventional banks or financial institutions. LKS was originally offered as a sharia-compliant financial organization for Muslims who want to escape the practice of banks or traditional financial institutions that use the interest system, but they can also be a choice for non-Muslims. Therefore, there are problems why the application of Sharia principles by LKS is an urgent problem and what are the conditions for applying Sharia principles by LKS. The research method used is normative legal research with a case approach. The study results indicate that the LKS organizer is expected to have a vision in which the LKS remains in the principles of Sharia.